TAMBAHAN BIAYA PADA TRANSAKSI PEMBAYARAN SISTEM PAYLATER DI MAKETPLACE DALAM PERSPEKTIF AKAD MUAMALAH KONTEMPORER - Bariroh, Muflihatul (Ahkam: Jurnal Hukum Islam, 2024)
This article aims to examine in depth and try to emphasize understanding regarding the emergence of a discourse and debate among the Muslim community regarding the legality of the paylater practice which has raised doubts among Muslims because several previous literatures stated that the use of the pay later method is prohibited because of the additional costs of the total principal expenditure which is indicated contains usury. Paylater itself or the pay later system is one of the new digital payment systems in today's marketplace without using a credit card. Paylater offers convenience facilities for platform users in shopping so they can make payments at a later date. This research method is a qualitative type which is prescriptive descriptive using an instrumental case study type approach. This approach is used to express a deep and detailed picture of a situation or object, where the author aims at a deep understanding of an issue or reformulating a theoretical explanation. The research results show that additional costs in the paylater payment system by platform users have not automatically considered usury. Through in-depth understanding, with the option of using a taqsith sale and purchase contract and/or a kafalah bil ujrah contract, the addition of the paylater payment system can be justified. These additional costs can act as a margin in buying and selling or can act as a fee or reward in a kafalah bil ujrah contract, such as fees in sharia card practices.